Anatomía de la madera de ocho especies de la selva mediana subperennifolia de Quintana Roo, México - Rebollar Domínguez, Silvia (1996)
This paper describes the wood anatomy of Ficus tecolutensis (Liebm.) Miq., Coccoloba acapulcensis Stand!., Lysiloma latisiliqua (L.) Benth., Caesalpinia gaumeri G., Alvaradoa amorphoides Liebm., Thouinia paucidentata Radlk., Tabebuia chrysantha (Jacq.) Nicholson and Guettarda combsii Urb. from Quintana Roo state, Mexieo. Interest is based on their local uses as rustic house constructions, fumiture and handtools. For each. species one tree was collected and the macroscopic and microscopic features were studied through wood samples, .permanent slides and macerated material. These species have diffuse porosity, simple perforation plates, alternate vessel pits, small rays and ergastic cantains. However, they differ in vessel arrangement, type ofaxial' ilnd radial parenchyma and fibre wall thickness: Anatomical features show that all species can be prommoted to the·market.